Shop class as soulcraft : an inquiry into the value of work - Crawford, Matthew B. (Penguin Press, 2009)
In this wise and often funny book, a philosopher/mechanic systematically destroys the pretensions of the high-prestige workplace and makes an irresistible case for working with one's hands.